Solid electrolyte membrane and preparation method and application thereof

By self-assemblying the polyoxazoline ionic conductor with the film-forming agent and zinc salt, a high-strength and high-toughness solid electrolyte membrane was prepared, which solved the problem of electrochemical performance deterioration of zinc ion batteries at low temperatures, and achieved efficient ion conduction and excellent electrochemical performance.

CN119542569APending Publication Date: 2025-02-28NORTHEAST NORMAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411522165.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing zinc ion batteries have reduced the conductivity of electrolytes and increased interface impedance at low temperatures, resulting in deterioration of electrochemical performance, and the porous aromatic skeleton materials are difficult to process into films, limiting their application.

Method used

The porous aromatic framework is used to self-assemble the polyoxazoline ion conductor, and the hydrogen bonding of the sulfonated porous aromatic framework and the polyoxazoline chain is formed to form a high-strength, high-toughness solid electrolyte membrane, and combined with the film forming agent and zinc salt to prepare a film with high ionic conductivity and low glass transition temperature.

Benefits of technology

It significantly improves the ion conductivity and electrochemical performance of all-solid zinc ion batteries at low temperatures, achieving high discharge capacity, excellent rate performance and excellent cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005108291840000011
    Figure HDA0005108291840000011
  • Figure HDA0005108291840000012
    Figure HDA0005108291840000012
  • Figure HDA0005108291840000021
    Figure HDA0005108291840000021
Patent Text Reader

Abstract

The invention discloses a solid electrolyte membrane and a preparation method and application thereof, and belongs to the technical field of electrolyte. The solid electrolyte membrane is composed of a porous aromatic skeleton self-assembled polyoxazoline ion conductor, a film-forming agent and a zinc salt, the porous aromatic skeleton self-assembled polyoxazoline ion conductor is composed of a sulfonated porous aromatic skeleton and a polyoxazoline chain generated by initiating polymerization in pores of the sulfonated porous aromatic skeleton; the sulfonated porous aromatic skeleton is connected with the polyoxazoline chain through a hydrogen bond. The solid electrolyte membrane is uniform, smooth, transparent, free of phase separation, high in ionic conductivity and low in glass transition temperature, and the all-solid-state zinc ion battery prepared from the solid electrolyte membrane has high discharge capacity, excellent rate capability and excellent cycling stability at low temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrolyte technology, and in particular to a solid electrolyte membrane, its preparation method, and its application. Background Technology

[0002] Zinc-ion batteries (ZIBs) are typically combined with aqueous electrolytes and are considered promising next-generation energy storage devices due to their high theoretical capacity (820 mAh / g), inherent safety, and low cost. However, ZIBs face several challenges in practical applications, such as irreversible dendrite growth and corrosion of the zinc anode, unavoidable side reactions (hydrogen evolution reaction (HER)), and a narrow electrochemical window leading to lower energy density. These adverse side reactions increase interfacial resistance, reduce the utilization efficiency of the zinc anode, and consequently shorten the battery's storage life.

[0003] Currently, most research on zinc-ion batteries focuses on developing higher-capacity cathode materials, optimizing the cycle performance of zinc anodes, anode protection, and separator modification. However, most of these studies suffer from significant drawbacks such as high cost and complex fabrication processes. Inspired by research on all-solid-state lithium batteries, developing highly stable all-solid-state ZIBs is an effective strategy to address these issues.

[0004] However, as demands for battery performance increase, the need for developing all-solid-state Zinc-ion batteries that maintain high energy density under low-temperature conditions has become more urgent. At low temperatures (≤0℃), the ionic conductivity of solid electrolytes decreases significantly, and the impedance at the electrolyte-electrode interface increases, leading to a rapid deterioration in the battery's electrochemical performance. Therefore, improving the performance of solid electrolytes at low temperatures is crucial for advancing the application of all-solid-state Zinc-ion batteries. Porous aromatic framework ionic conductor electrolytes (SPAFs) covalently fix anions in a stable framework structure, thus suppressing anion migration; ideally, only cation migration occurs. However, because porous aromatic framework materials are often in solid powder form, they are difficult to process into films and have poor dispersibility in organic solvents, limiting further practical applications. Simultaneously, the high concentration of anions leads to excessive electrostatic interactions between them and zinc ions, restricting zinc ion transport within the framework and resulting in low ionic conductivity in SPAF-based all-solid-state zinc-ion batteries.

[0005] Therefore, it is of great significance to research and develop a novel solid electrolyte based on a porous aromatic framework to improve the ionic conductivity of all-solid-state zinc-ion batteries. Summary of the Invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a solid electrolyte membrane, its preparation method, and its application. The solid electrolyte membrane has high ionic conductivity and low glass transition temperature, and the all-solid-state zinc-ion battery prepared using it has high discharge capacity, excellent rate performance, and excellent cycle stability at low temperatures.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0008] This invention provides a solid electrolyte membrane composed of a porous aromatic framework self-assembled polyoxazoline ion conductor, a film-forming agent, and a zinc salt;

[0009] The porous aromatic framework self-assembled polyoxazoline ionic conductor consists of a sulfonated porous aromatic framework and polyoxazoline chains generated by in-pore polymerization.

[0010] The sulfonated porous aromatic skeleton and the polyoxazoline chain are connected by hydrogen bonds.

[0011] The polyoxazoline described in this invention includes, but is not limited to, poly(2-methyl-2-oxazoline), poly(2-ethyl-2-oxazoline), poly(2-propyl-2-oxazoline), and poly(2-butyl-2-oxazoline).

[0012] In this invention, the polyoxazoline is preferably poly(2-ethyl-2-oxazoline) or poly(2-methyl-2-oxazoline).

[0013] The hydrogen bonds are formed by the nitrogen and oxygen on the polyoxazoline structure and the hydrogen on the sulfonic acid groups in the sulfonated porous aromatic framework.

[0014] Preferably, the thickness of the solid electrolyte membrane is 10-200 μm; more preferably, it is 50-120 μm. In some specific embodiments of the present invention, it is preferably 78 μm. Preferably, the film-forming agent is selected from polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride (PVDF), or polyethylene oxide (PEO); more preferably, it is polyvinylidene fluoride (PVDF).

[0015] In a further preferred embodiment of the present invention, the molecular weight of the polyvinylidene fluoride is 100-2000 kDa; even more preferably, it is 100-500 kDa. In some specific embodiments of the present invention, it is preferably 150 kDa.

[0016] Preferably, the zinc salt is selected from zinc trifluoromethanesulfonate, zinc sulfate, or zinc acetate; more preferably, it is zinc trifluoromethanesulfonate.

[0017] The film-forming agent serves as a mechanical support, and the zinc salt provides zinc ions to achieve ion transport.

[0018] This invention ingeniously combines a stable sulfonated porous aromatic framework with a flexible polyoxazoline chain to obtain a supramolecular assembly that combines rigidity and flexibility. Specifically, the sulfonated porous aromatic framework acts as a macromolecular initiator for the cationic ring-opening polymerization of oxazoline, enabling confined in-situ polymerization within the pores of the sulfonated porous aromatic framework to obtain the polyoxazoline chain. The two then self-assemble into a single unit through hydrogen bonding, resulting in a solid electrolyte membrane with high strength and toughness.

[0019] The sulfonic acid groups in the rigid and stable sulfonated porous aromatic framework of the solid electrolyte membrane described in this invention can provide a sufficiently long nanoscale buffer channel for the uniform deposition and stripping of zinc ions. The solvation effect of the confined growth of flexible polyoxazoline chains can make it easier for zinc ions to decouple from the sulfonic acid groups on the pore walls of the sulfonated porous aromatic framework, thereby achieving efficient transport of zinc ions and significantly improving the performance of all-solid-state zinc-ion batteries at low temperatures.

[0020] The porous aromatic framework self-assembled polyoxazoline ionic conductor described in this invention exhibits excellent dispersibility in a polymer matrix (i.e., film-forming agent). This is because polyoxazoline chains are grafted into the pores of the sulfonated porous aromatic framework. The porous aromatic framework self-assembled polyoxazoline ionic conductor can form a stable, sediment-free suspension in organic solvents, thereby making the dried and shaped solid electrolyte membrane uniform, smooth, and transparent, without phase separation.

[0021] The solid electrolyte membrane described in this invention possesses excellent mechanical properties and high ionic conductivity. The solid electrolyte membrane exhibits outstanding ionic conductivity in the low-temperature region, nearly 50 times that of pure polyvinylidene fluoride membranes. This is due to the presence of polyoxazoline chains, which enhances polymer kinetics and lowers the glass transition temperature of the solid electrolyte membrane described in this invention.

[0022] Preferably, the porous aromatic skeleton in the sulfonated porous aromatic skeleton is selected from PAF-1, PAF-5, PAF-100, PAF-154, PAF-155, PAF-158 or PAF-159.

[0023] The present invention also provides a method for preparing the above-mentioned solid electrolyte membrane, comprising the following steps:

[0024] (1) The porous aromatic framework material and chlorosulfonic acid were mixed and reacted to obtain the sulfonated porous aromatic framework material;

[0025] (2) The sulfonated porous aromatic framework material, oxazoline, and solvent are mixed and heated to react and obtain a porous aromatic framework self-assembled polyoxazoline ionic conductor.

[0026] (3) The porous aromatic framework self-assembled polyoxazoline ion conductor is mixed with polyvinylidene fluoride, zinc trifluoromethanesulfonate and organic solution, and then shaped and dried to obtain the solid electrolyte membrane.

[0027] In the above preparation method, the sulfonated porous aromatic framework material (SPAF) in step (2) serves both as an initiator and as a confined space for the growth of oxazoline. This is because the sulfonated porous aromatic framework material contains sulfonic acid groups that act as Lewis acids, which are subjected to nucleophilic attacks from the lone pair electrons on the nitrogen atoms of the oxazoline. This results in the SPAF losing its protons and existing as a large equilibrium anion, further leading to the formation of an oxazoline cationic intermediate during the chain induction process of the polyoxazoline. Then, during chain growth, the oxazoline monomer in the solution attacks the oxazoline cationic intermediate, causing the oxazoline monomer to open its ring, forming an amide bond and ultimately forming a polyoxazoline chain.

[0028] Preferably, in step (2), the mass ratio of the sulfonated porous aromatic framework material to the oxazoline is 1:(1-5); more preferably, it is 1:1.

[0029] Preferably, the heating temperature in step (2) is 30℃-150℃; more preferably, it is 70℃-100℃. In some specific embodiments of the present invention, 80℃ is preferred.

[0030] After the reaction is completed in step (2), the process also includes filtration, washing, and drying.

[0031] The present invention does not impose any particular limitation on the washing solvent, filtration method and drying method, which can be any solvent or method known in the art.

[0032] In this invention, the washing solvent is preferably one or more of acetonitrile, ethanol, and water. In some specific embodiments of this invention, the washing is performed three times each using acetonitrile, ethanol, and water.

[0033] Preferably, in step (1), the mass ratio of the porous aromatic framework material to chlorosulfonic acid is (90-110):1; more preferably (95-105):1; and even more preferably 100:1.

[0034] Preferably, step (1) includes the following steps:

[0035] The porous aromatic framework (PAF) powder was dispersed in ice water, and chlorosulfonic acid was slowly added dropwise. The mixture was kept warm and stirred in an ice water bath to carry out full sulfonation, thus obtaining a sulfonated porous aromatic framework material.

[0036] After the reaction in step (1) is completed, post-processing such as filtration, washing, and drying is also included.

[0037] The present invention does not impose any particular limitation on the filtration, washing, and drying processes; any method known to those skilled in the art is acceptable.

[0038] The drying process is preferably vacuum drying.

[0039] The vacuum drying temperature is preferably 90℃-100℃; more preferably 100℃.

[0040] The vacuum drying time is preferably 8-14 h; more preferably 12 h. Preferably, in step (3), the mass ratio of the porous aromatic framework self-assembled polyoxazoline ionic conductor and polyvinylidene fluoride is (0.005-1):(5-10); more preferably (0.005-0.5):(5-7); and even more preferably 0.001:1.

[0041] Preferably, in step (3), the mass ratio of polyvinylidene fluoride to zinc trifluoromethanesulfonate is (5-10):(5-10). In some specific embodiments of the present invention, a ratio of 1:1 is preferred.

[0042] Preferably, the solution in step (2) of this invention is selected from one or more of acetonitrile, toluene, DMF, THF, and chloroform; more preferably, it is acetonitrile or chloroform; and even more preferably, it is acetonitrile.

[0043] Preferably, the organic solution in step (3) is selected from N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, or dimethyl sulfoxide. In some specific embodiments of the present invention, N,N-dimethylformamide is preferred.

[0044] In the above preparation method of the present invention, the shaping and drying methods in step (3) are not particularly limited, and any method known to those skilled in the art is acceptable.

[0045] The shaping is preferably casting shaping, and the drying is preferably oven drying.

[0046] The drying temperature in the oven is preferably 70℃-90℃, and more preferably 80℃.

[0047] The present invention also provides the application of the above-described solid electrolyte membrane or the solid electrolyte membrane prepared by the above-described preparation method in zinc-ion batteries.

[0048] The zinc-ion batteries include, but are not limited to, all-solid-state zinc-ion batteries and quasi-solid-state zinc-ion batteries.

[0049] The present invention also provides an all-solid-state zinc-ion battery, comprising the solid electrolyte membrane described above or the solid electrolyte membrane prepared by the above preparation method.

[0050] The all-solid-state zinc-ion battery has high discharge capacity, excellent rate performance, and excellent cycle stability.

[0051] The all-solid-state zinc-ion battery consists of zinc foil, the aforementioned solid electrolyte membrane, and a positive electrode sheet.

[0052] The method for preparing the positive electrode sheet includes the following steps:

[0053] (1) First, mix the active material, acetylene black, polyvinylidene fluoride and N-methylpyrrolidone to obtain the positive electrode slurry;

[0054] (2) Coat the positive electrode slurry evenly onto the stainless steel mesh, dry it, and cut it into round pieces, which are the positive electrode sheets.

[0055] The active substance in step (1) is selected from vanadium pentoxide, manganese dioxide, Maxene, graphite, graphynylene, graphene, zinc cobaltate, or zinc iron phosphate.

[0056] The active substance, acetylene black, and polyvinylidene fluoride in step (1) are in a mass ratio of (6-10):1:1; more preferably 8:1:1.

[0057] The preferred mixing step (1) involves first mixing the active material, acetylene black, and polyvinylidene fluoride, and then adding N-methylpyrrolidone.

[0058] The mixing in step (1) is preferably a grinding mixture.

[0059] The coating process in step (2) is preferably applied by scraping.

[0060] The drying temperature in step (2) is preferably 50℃-150℃, and the drying time is preferably 24-72h.

[0061] In some specific embodiments of the present invention, the all-solid-state zinc-ion battery is composed of zinc foil / SPP@PVDF / vanadium pentoxide, which has a high discharge capacity of 387mAh / g at 1C.

[0062] The all-solid-state zinc-ion battery with the above composition of zinc foil / SPP@PVDF / vanadium pentoxide also has excellent rate performance, reaching 225mAh / g at 10C.

[0063] The all-solid-state zinc-ion battery with the above composition of zinc foil / SPP@PVDF / vanadium pentoxide also has excellent low-temperature cycle stability. It can stably cycle 280 times at -40℃ with a coulombic efficiency of 100%.

[0064] The preparation method of the all-solid-state zinc-ion battery includes the following steps:

[0065] The solid electrolyte membrane described in this invention is placed between the zinc foil and the positive electrode sheet, and then pressed for 5-50 seconds under a pressure of 40-60 MPa using a battery sealing machine to obtain the all-solid-state zinc-ion battery.

[0066] The present invention also provides the application of the above-mentioned all-solid-state zinc-ion battery in low-temperature energy storage materials, wherein the low temperature is ≤0℃.

[0067] The all-solid-state zinc-ion battery described in this invention has the advantages of high safety, high stability and long cycle life.

[0068] Compared with existing technologies, the solid electrolyte membrane provided by this invention is composed of a porous aromatic framework self-assembled polyoxazoline ionic conductor, a film-forming agent, and a zinc salt. The porous aromatic framework self-assembled polyoxazoline ionic conductor consists of a sulfonated porous aromatic framework and polyoxazoline chains generated by in-pore polymerization. The sulfonated porous aromatic framework and the polyoxazoline chains are connected by hydrogen bonds. The solid electrolyte membrane is uniform, smooth, transparent, and free from phase separation. It also exhibits high ionic conductivity and a low glass transition temperature. All-solid-state zinc-ion batteries prepared using this membrane possess high discharge capacity, excellent rate performance, and excellent cycle stability at low temperatures. Attached Figure Description

[0069] Figure 1 Infrared spectra of poly(2-ethyl-2-oxazoline) (PEtOx) and SPAF-1 and SPP prepared in Example 1;

[0070] Figure 2 Transmission electron microscopy (TEM) characterization image (a) and small-angle X-ray scattering (SAXS) spectrum (b) of an ultrathin section of the solid electrolyte membrane prepared in Example 1;

[0071] Figure 3 A cross-sectional scanning electron microscope image of the solid electrolyte membrane prepared in Example 1;

[0072] Figure 4 Figure a shows the temperature-dependent impedance spectrum of the solid electrolyte prepared in Example 1, and Figure b is a magnified view of the part within the red dashed box in Figure a.

[0073] Figure 5 This is an electrochemical window test curve of the solid electrolyte membrane prepared in Example 1 after it was assembled into a battery;

[0074] Figure 6 The zinc foil / SPP@PVDF / zinc foil symmetric cell prepared using the solid electrolyte membrane obtained in Example 1 was tested at a current density of 1 mA / cm². 2 Zinc ion polarization cycle curves below;

[0075] Figure 7The graph shows the rate charge-discharge curves of the zinc foil / SPP@PVDF / vanadium pentoxide all-solid-state battery prepared using the solid electrolyte membrane obtained in Example 1 at 1–10C.

[0076] Figure 8 Cyclic stability curves of zinc foil / SPP@PVDF / vanadium pentoxide all-solid-state batteries prepared using the solid electrolyte membrane obtained in Example 1 at -40°C and 1C.

[0077] Figure 9 The graph shows the cycle stability of the zinc foil / SPP@PVDF / vanadium pentoxide all-solid-state battery prepared using the solid electrolyte membrane obtained in Example 1 at -40°C and 1C. Detailed Implementation

[0078] To further illustrate the present invention, the solid electrolyte membrane, its preparation method, and its application provided by the present invention will be described in detail below with reference to embodiments.

[0079] Unless otherwise specified, all materials, reagents, apparatus, instruments, and equipment used in the following examples are commercially available.

[0080] (I) Preparation of solid electrolyte membranes based on porous aromatic frameworks

[0081] Example 1

[0082] Step 1: Disperse 100 mg of porous aromatic framework (PAF-1) powder into 10 mL of ice water, slowly add 1 mL of chlorosulfonic acid, and stir in an ice-water bath for 72 h to ensure complete sulfonation. After the reaction is complete, discharge the product into water, filter, wash thoroughly with deionized water, collect the solid powder, and vacuum dry at 100 °C for 12 h to obtain blue sulfonated porous aromatic framework (SPAF-1);

[0083] Step 2: 100 mg SPAF-1 and 10 mL of acetonitrile solution of 2-ethyl-2-oxazoline monomer (3 mg / mL) were reacted at 80 °C for 48 h. After the reaction was completed, the mixture was filtered, washed three times with water, and dried under vacuum to obtain porous aromatic framework self-assembled poly(2-ethyl-2-oxazoline) ionic conductor (SPP).

[0084] Step 3: First, dissolve 500 mg of polyvinylidene fluoride (molecular weight 150 kDa) and 500 mg of zinc trifluoromethanesulfonate in N,N-dimethylformamide to obtain a polymer slurry. Then, mix this slurry with 0.5 mg of porous aromatic framework self-assembled poly(2-ethyl-2-oxazoline) ion conductor. Cast the resulting slurry into a mold and dry it in an 80°C oven to remove N,N-dimethylformamide, obtaining a porous aromatic framework self-assembled poly(2-ethyl-2-oxazoline) solid electrolyte membrane (SPP@PVDF). The poly(2-ethyl-2-oxazoline) is PEtOx.

[0085] Figure 1 The infrared spectra of SPAF, SPP, and PEtOx are shown, indicating the successful preparation of these materials. Furthermore, the presence of numerous hydrogen bond acceptors on PEtOx leads to the formation of numerous hydrogen bonds between PEtOx and the sulfonated porous aromatic framework (SPAF). Fourier transform infrared spectroscopy reveals a characteristic peak for amide bonds at 1636 cm⁻¹ in SPP, consistent with PEtOx, confirming the successful introduction of the PEtOx chain. Compared to SPAF, the characteristic peak of the sulfonic acid group in SPP exhibits a redshift. This is due to the hydrogen bonding interactions between the oxygen and nitrogen groups in PEtOx and the sulfonic acid groups, resulting in a decrease in the stretching vibration frequency. This suggests that SPAF and PEtOx in SPP are linked through hydrogen bonding interactions.

[0086] Comparative Example 1

[0087] Similar to Example 1, except that the polymerization of poly(2-ethyl-2-oxazoline) chains was not confined and initiated in situ within the porous aromatic framework pores. The specific operation is as follows:

[0088] Step 1: Disperse 100 mg of porous aromatic framework (PAF-1) powder into 10 mL of ice water, slowly add 1 mL of chlorosulfonic acid, and stir in an ice-water bath for 72 h to ensure complete sulfonation. After the reaction is complete, discharge the product into water, filter, wash thoroughly with deionized water, collect the solid powder, and vacuum dry at 100 °C for 12 h to obtain blue sulfonated porous aromatic framework (SPAF-1);

[0089] Step 2: First, dissolve 500 mg of polyvinylidene fluoride and 500 mg of zinc trifluoromethanesulfonate in N,N-dimethylformamide to obtain a polymer slurry. Then, mix it with 0.5 mg of blue sulfonated porous aromatic framework evenly. Cast the resulting slurry into a mold and dry it in an 80°C oven to remove N,N-dimethylformamide, thus obtaining a sulfonated porous aromatic framework solid electrolyte membrane (SPAF@PVDF).

[0090] (II) Performance testing of the solid electrolyte membranes prepared in Example 1 and Comparative Example 1

[0091] 1. The microstructure of the nanophases in SPP@PVDF ultrathin slices was observed using transmission electron microscopy (TEM). Figure 2 As shown in Figure a, the porous aromatic framework self-assembled poly(2-ethyl-2-oxazoline) ionic conductor exhibits high compatibility with the polymer aggregate PVDF, with a smooth and uniform membrane surface and no phase separation observed. This indicates that the introduction of the porous aromatic framework self-assembled poly(2-ethyl-2-oxazoline) ionic conductor did not disrupt the inherent microphase structure of PVDF. Further small-angle X-ray scattering (SAXS) was used to investigate the microphase structure of the membrane, from... Figure 2 As can be seen from Figure b, the pure PVDF membrane in There is a peak at a certain position, and the position of this peak did not change after the introduction of SPP, proving the perfect preservation of the nanophase in the SPP@PVDF film. In contrast, the SPAF@PVDF film... A broad peak is shown at [location]. Another scattering peak with enhanced intensity was observed at this point, indicating significant phase separation in the SPAF@PVDF film.

[0092] Figure 3 A cross-sectional scanning electron microscope (SEM) image of the solid electrolyte membrane prepared in Example 1 shows that the cross-sectional thickness of the solid electrolyte membrane is 78 micrometers. 2. The ionic conductivity of SPP@PVDF was evaluated using AC impedance spectroscopy. Figure 4 As shown, the resistance decreases with increasing temperature, while the ionic conductivity gradually increases. This is due to the enhanced polymer chain kinetics at high temperatures. Experimental results show that the ionic conductivity of the SPP@PVDF of this invention reaches as high as 5.04 × 10⁻⁶ at room temperature. -4 S cm -1 The zinc ion transference number is as high as 0.82. In addition, SPP@PVDF exhibits outstanding ionic conductivity in the low-temperature region, which is nearly 50 times that of pure polyvinylidene fluoride membrane. This is due to the presence of poly(2-ethyl-2-oxazoline) chains, which enhances polymer kinetics and thus lowers the glass transition temperature of the solid electrolyte membrane.

[0093] 3. The electrochemical stability window is measured using linear sweep voltammetry (LSV), such as... Figure 5 As shown, the electrochemical window of SPP@PVDF is as high as 2.74V, which is wider than that of 2M zinc trifluoromethanesulfonate aqueous solution (1.9V), indicating that the introduction of poly(2-ethyl-2-oxazoline) significantly enhances the high voltage tolerance of the electrolyte.

[0094] 4. Benefiting from the material's rapid zinc ion transport channels and abundant nucleation sites, SPP@PVDF can impart excellent cycling performance to the zinc anode. Zinc foil / SPP@PVDF / zinc foil symmetric cells were fabricated, and constant current electroplating / peeling tests were conducted. Figure 6 The figure shown is at 1mA / cm 2 At current densities of [value missing], the symmetric cell based on SPP@PVDF maintains stable polarization for over 2200 hours, indicating that it has a long cycle life.

[0095] 5. Assemble zinc foil / SPP@PVDF / vanadium pentoxide all-solid-state batteries and conduct rate performance tests at 1–10C. For example... Figure 7 As shown in the figure, after testing, the charge and discharge capacity curves at room temperature basically overlap. The zinc foil / SPP@PVDF / vanadium pentoxide all-solid-state battery has high discharge capacity (387mAh / g at 1C) and excellent rate performance (225mAh / g at 10C).

[0096] 6. Assemble zinc foil / SPP@PVDF / vanadium pentoxide all-solid-state batteries and conduct variable-temperature charge-discharge tests, such as... Figure 8 As shown in the figure, the charge and discharge capacity curves basically overlap. The zinc foil / SPP@PVDF / vanadium pentoxide all-solid-state battery has a specific capacity of 139mAh / g at -40℃ and a capacity retention rate of 35.9% (relative to room temperature).

[0097] 7. Assemble a zinc foil / SPP@PVDF / vanadium pentoxide all-solid-state battery and test its cycle stability at -40℃. Figure 9 As shown, the charge-discharge capacity curves in the figure basically overlap. The zinc foil / SPP@PVDF / vanadium pentoxide all-solid-state battery can stably cycle 280 times at -40℃, and the coulombic efficiency remains above 100%. The description of the embodiments is only for the purpose of helping to understand the method and core idea of ​​the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principle of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.

Claims

1. A solid electrolyte membrane, characterized in that: It is composed of a porous aromatic framework self-assembled polyoxazoline ion conductor, a film-forming agent and a zinc salt; The porous aromatic skeleton self-assembled polyoxazoline ion conductor is composed of a sulfonated porous aromatic skeleton and polyoxazoline chains generated by initiating polymerization in the pores thereof; The sulfonated porous aromatic framework and the polyoxazoline chains are connected by hydrogen bonds.

2. The solid electrolyte membrane according to claim 1, characterized in that The thickness of the solid electrolyte membrane is 10-200 μm.

3. The solid electrolyte membrane according to claim 1, characterized in that The film-forming agent is selected from polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride or polyethylene oxide; The zinc salt is selected from zinc trifluoromethanesulfonate, zinc sulfate or zinc acetate.

4. The solid electrolyte membrane according to any one of claims 1 to 3, characterized in that: The porous aromatic skeleton in the sulfonated porous aromatic skeleton is selected from PAF-1, PAF-5, PAF-100, PAF-154, PAF-155, PAF-158 or PAF-159.

5. The method for preparing a solid electrolyte membrane according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing a porous aromatic skeleton material and chlorosulfonic acid to obtain a sulfonated porous aromatic skeleton material; (2) mixing and heating the sulfonated porous aromatic skeleton material, oxazoline, and a solvent to obtain a porous aromatic skeleton self-assembled polyoxazoline ion conductor; (3) The porous aromatic skeleton self-assembled polyoxazoline ion conductor is mixed with polyvinylidene fluoride, zinc trifluoromethanesulfonate and an organic solution, and the mixture is shaped and dried to obtain the solid electrolyte membrane.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the sulfonated porous aromatic framework material to oxazoline in the step (2) is 1:(1-5); The heating temperature in step (2) is 30°C-150°C.

7. The preparation method according to claim 5, characterized in that: The mass ratio of the porous aromatic skeleton material to chlorosulfonic acid in step (1) is (90-110):1; The mass ratio of the porous aromatic skeleton self-assembled polyoxazoline ion conductor to polyvinylidene fluoride in step (3) is (0.005-1): (5-10); The mass ratio of polyvinylidene fluoride to zinc trifluoromethanesulfonate in the step (3) is (5-10): (5-10).

8. Use of the solid electrolyte membrane according to any one of claims 1 to 4 or the solid electrolyte membrane prepared by the preparation method according to any one of claims 5 to 7 in a zinc ion battery.

9. An all-solid-state zinc ion battery, characterized in that: The invention comprises the solid electrolyte membrane according to any one of claims 1 to 4 or the solid electrolyte membrane prepared by the preparation method according to any one of claims 5 to 7.

10. Use of the all-solid-state zinc ion battery according to claim 9 in low-temperature energy storage materials, wherein the low temperature is ≤0°C.

Citation Information

Cited By

  • Electrochemical sensor for uric acid detection and preparation method thereof

    CN120668751A